An Inorganic‐Rich Solid Electrolyte Interphase for Advanced Lithium‐Metal Batteries in Carbonate Electrolytes - Liu, Sufu; Ji, Xiao; Piao, Nan; Chen, Ji; Eidson, Nico; Xu, Jijian; Wang, Pengfei; Chen, Long; Zhang, Jiaxun; Deng, Tao; Hou, Singyuk; Jin, Ting; et al. (Angewandte Chemie International Edition, 2021)
In carbonate electrolytes, the organic–inorganic solid electrolyte interphase (SEI) formed on the Li‐metal anode surface is strongly bonded to Li and experiences the same volume change as Li, thus it undergoes continuous cracking/reformation during plating/stripping cycles. Here, an inorganic‐rich SEI is designed on a Li‐metal surface to reduce its bonding energy with Li metal by dissolving 4m concentrated LiNO3 in dimethyl sulfoxide (DMSO) as an additive for a fluoroethylene‐carbonate (FEC)‐based electrolyte. Due to the aggregate structure of NO3− ions and their participation in the primary Li+ solvation sheath, abundant Li2O, Li3N, and LiNxOy grains are formed in the resulting SEI, in addition to the uniform LiF distribution from the reduction of PF6− ions. The weak bonding of the SEI (high interface energy) to Li can effectively promote Li diffusion along the SEI/Li interface and prevent Li dendrite penetration into the SEI. As a result, our designed carbonate electrolyte enables a Li anode to achieve a high Li plating/stripping Coulombic efficiency of 99.55 % (1 mA cm−2, 1.0 mAh cm−2) and the electrolyte also enables a Li||LiNi0.8Co0.1Mn0.1O2 (NMC811) full cell (2.5 mAh cm−2) to retain 75 % of its initial capacity after 200 cycles with an outstanding CE of 99.83 %. An inorganic‐rich solid electrolyte interphase (SEI) has been constructed on Li metal to promote dense Li growth with a Coulombic efficiency of 99.55 % in the carbonate electrolyte. It was synthesized on the surface of the Li‐metal anode using concentrated LiNO3 in dimethyl sulfoxide (DMSO) as an additive in the FEC‐based electrolyte, which participates in the primary Li+ solvation shell and promotes the reduction of NO3− ions to form the inorganic‐rich SEI.